Men's Glee Club 1941-1942 (1941)
Men's Glee Club, 1941-1942 (left to right): At the piano: Gil Brown and Director H. P. Davidson. First row: Ray Rabjohn, Delbert Smith, Alex Spanos, Charles Morris, Don Woods, Bob Winans, Jack Kleck, Gail Allen, Dick Wasson, Bill Struckmeyer, Kenneth Taylor, Danny Spanos, John Dutton, Walter Dougherty, Raymond Schwab. Second row: Ben Barr, Leroy Kawahara, Bryant Ehrenborg, Ted Wardell, John Nicolaides, Dave Risling, Ralph Carlsen, Morris Markee, Ted Hollinger, Bob Winterbourne, Ray Raybourn, Chester McCorkle, Fred Kobayashi, Loren McNicholl and Alvin Quist.